Piroxicam encapsulated in liposomes: Characterization and in vivo evaluation of topical anti-inflammatory effect - Canto, G. S.; Dalmora, S. L.; Oliveira, Anselmo Gomes de [UNESP] (Marcel Dekker Inc, 1999)
Liposomes of soya phosphatidylcholine, cholesterol, and stearylamine (molar ratio 6/3/1) and 0.1% alpha-tocopherol were prepared by the extrusion of multilamellar vesicles through 0.2-mu m polycarbonate membrane. Liposomes were characterized by electron transmission microscopy, and the mean structure diameter was 278 nm. The encapsulation efficiency obtained was 12.73%. The topical anti-inflammatory effect was evaluated in vivo by the cotton pellet granuloma method. We analyzed free piroxicam at 4 mg/kg, piroxicam encapsulated in liposomes added to 1.5% hydroxyethylcellulose (HEC) gel at 1.6 mg/kg, and piroxicam encapsulated in liposomes added to HEC gel at 4 mg/kg; the inhibition of inflammation obtained was 21.1%, 32.8%, and 47.4%, respectively. These results showed that the encapsulation of piroxicam produced an increase of topical anti-inflammatory effect, suggesting that the inhibition of inflammation can be obtained with lower drug concentrations.